Shocking decision of the jury and their reception – the role of film critics in shaping the image of the Gdynia Film Festival - Sowiński, Emil (Death of the Critic: Participatory Culture and the Transformations of Criticism in the 20th and 21st Centuries, 2022)
Reception studies is usually devoted to films, which caused controversy and political strife, and those that are assigned a significant role in shaping historical consciousness. The purpose of this article is analyze the film critic reception of the verdicts of the jury of the Gdynia Film Festival. Thereupon my primary interest will be the most important polish film festival and press coverage (1990-2017)